Smart Solutions in Elderly Care Facilities with RFID System and Its Integration with Wireless Sensor Networks. (27th August 2014) - Joshi, Gyanendra Prasad; Acharya, Srijana; Kim, Chang-Su; Kim, Byung-Seo; Kim, Sung Won
Abstract : Healthcare and medical advances have prolonged human life and thus have led to increasing numbers of elderly individuals. To make their lives more convenient, several ubiquitous technologies have been considered, including the RFID system, which can play a vital role in elderly care by caregivers as well as by elderly individuals themselves. Caregivers can take advantage of the RFID system by recording and tracking elderly individuals' belongings and assisting these individuals in healthcare provision by accessing their relevant information, among others. Similarly, the RFID system can help manage elderly individuals' daily lives by reminding them of their daily schedules (e.g., reminding them to take medicine on time) and tracking their personal belongings, among others. In addition, the RFID system can mitigate human errors such as medical mistakes, delays in service provision, and hassles in tracking and identifying patients and objects. This study provides a survey of solutions proposed in the literature and discusses the potential benefits of integrating the RFID system with sensors and applying the integrated system. In addition, the study addresses the opportunities, technological challenges, and research directions for the integrated RFID system in the context of smart solutions in elderly care facilities.